Development of Quizizz Paper Mode Based Learning Media in Science Learning at the Elementary School Level - Putri Inayah H.S; Nur Rahmah; Abdul Rahman Rahman; Muhammad Fasli (FKIP - Universitas Riau, 2026)
An interactive learning medium based on Quizizz Paper Mode was designed to enhance science instruction at the elementary level, especially on the topic of energy transformation. This study applied a Research and Development (R&D) method using the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. The product was tested on fourth-grade students, with data collected through expert validation forms, teacher and student response questionnaires, and pre-test and post-test assessments. Validation results demonstrated a very high level of feasibility, with scores of 86.67% from media experts and 93.33% from subject-matter experts. Practicality was also rated very highly, as indicated by a 90% positive response from teachers and 100% from students. Moreover, the implementation of Quizizz Paper Mode significantly improved students’ learning outcomes, reflected in the increase between pre-test and post-test scores. The media also enhanced students’ motivation and strengthened their conceptual understanding, with mastery of the material reaching 100%, indicating that Quizizz Paper Mode is an effective and appropriate alternative interactive medium for elementary science learning.